2016
DOI: 10.1007/s10988-016-9187-2
|View full text |Cite
|
Sign up to set email alerts
|

Modified numerals and maximality

Abstract: In this article, we describe and attempt to solve a puzzle arising from the interpretation of modified numerals like less than five and between two and five. The puzzle is this: such modified numerals seem to mean different things depending on whether they combine with distributive or non-distributive predicates. When they combine with distributive predicates, they intuitively impose a kind of upper bound, whereas when they combine with non-distributive predicates, they do not (they sometimes even impose a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 30 publications
(42 reference statements)
0
13
0
5
Order By: Relevance
“…It is well-known, however, that the requirement of being in a downward entailing environment is at times too lax. In quite a few places in the literature, it is suggested that not only should NPI environments be downward entailing, they should also not be upward entailing (Progovac 1993;Lahiri 1998;Gajewski & Hsieh 2014;Barker 2017). One illustration of this comes from singular definite descriptions.…”
Section: "Zero" and Negative Polarity Itemsmentioning
confidence: 99%
“…It is well-known, however, that the requirement of being in a downward entailing environment is at times too lax. In quite a few places in the literature, it is suggested that not only should NPI environments be downward entailing, they should also not be upward entailing (Progovac 1993;Lahiri 1998;Gajewski & Hsieh 2014;Barker 2017). One illustration of this comes from singular definite descriptions.…”
Section: "Zero" and Negative Polarity Itemsmentioning
confidence: 99%
“… 8 In principle there are analytical possibilities as to how UBELE may arise without the use of alternatives. One possibility is that scalar terms (like, ‘warm’) may be upper-bounded in virtue of the presence of a maximality operation as suggested for the analysis of quantificational expressions with numerals (see Kennedy, 2015 ; Buccola and Spector, 2016 ). The research on numerals suggests there is a strong bias to understand those expressions via something like maximality ( Geurts, 2006 ; Breheny, 2008 ).…”
mentioning
confidence: 99%
“…In the remainder of this remark, we present evidence that casts doubt on (5). We provide new arguments that the descriptive condition on NPI licensing, (1), must be environment-based (rather than operator-based), and must reference full sentential alternatives (rather than scalemates), thus replacing (5) (see, e.g., Kadmon & Landman 1993, Lahiri 1998, Homer 2008, Gajewski 2011, Chierchia 2004, 2013, Crnič 2014, 2019a,b, 2020, Buccola & Spector 2016 for further arguments). Specifically, we argue that the acceptability of a sentence instantiating an intervention configuration does not depend simply on the position that the relevant operator occupies in its scale, but rather depends on the logical relation that the pertinent constituent dominating the operator (i.e., the pertinent environment) bears to its alternatives.…”
Section: The Received Viewmentioning
confidence: 98%